Serine/Arginine-rich protein family of splicing regulators: New approaches to study splice isoform functions. (June 2019) - Morton, Mitchell; AlTamimi, Nadia; Butt, Haroon; Reddy, Anireddy S.N.; Mahfouz, Magdy
Highlights: Serine/arginine-rich (SR) proteins bind RNA and function in stress responses. Conserved SR proteins modulate alternative splicing and other aspects of RNA metabolism. New technologies (CRISPR/Cas, TRIBE) enable functional analysis of SR families and their splice isoforms. Abstract: Serine/arginine-rich (SR) proteins are conserved RNA-binding proteins that play major roles in RNA metabolism. They function as molecular adaptors, facilitate spliceosome assembly and modulate constitutive and alternative splicing of pre-mRNAs. Pre-mRNAs encoding SR proteins and many other proteins involved in stress responses are extensively alternatively spliced in response to diverse stresses. Hence, it is proposed that stress-induced changes in splice isoforms contribute to the adaptation of plants to stress responses. However, functions of most SR genes and their splice isoforms in stress responses are not known. Lack of easy and robust tools hindered the progress in this area. Emerging technologies such as CRISPR/Cas9 will facilitate studies of SR function by enabling the generation of single and multiple knock-out mutants of SR subfamily members. Moreover, CRISPR/Cas13 allows targeted manipulation of splice isoforms from SR and other genes in a constitutive or tissue-specific manner to evaluate functions of individual splice variants. Identification of the in vivo targets of SR proteins and their splice variants using the recently developed TRIBE (Targets of RNA-binding proteins Identified By Editing) and other methods will help unravel their mode of action and splicing regulatory elements under various conditions. These new approaches are expected to provide significant new insights into the roles of SRs and splice isoforms in plants adaptation to diverse stresses.